Diagnostic challenge of Creutzfeldt-Jakob disease in a patient with multimorbidity: a case-report - Amber Yaqub; Mohammad Kamran Ikram; Jeroen Blankevoort; Mohammad Arfan Ikram (BMC Neurology, 2023)
Abstract Background Creutzfeldt-Jakob disease (CJD) is a rapidly progressive and ultimately fatal neurodegenerative condition caused by prions. The clinical symptoms of CJD vary with its subtype, and may include dementia, visual hallucinations, myoclonus, ataxia, (extra)pyramidal signs and akinetic mutism. In the early course of disease however, several clinical symptoms of CJD may mimic those of co-existing morbidities. Case presentation We report a male in his 60s with a history of situs inversus totalis and Churg Strauss syndrome, who presented with speech fluency disturbances, neuropsychiatric symptoms and allodynia, a few months after becoming a widower. Initially presumed a bereavement disorder along with a flare-up of Churg Strauss, his symptoms gradually worsened with apraxia, myoclonic jerks and eventually, akinetic mutism. MRI revealed hyperintensities at the caudate nucleus and thalami, while the cerebrospinal fluid was positive for the 14-3-3 protein and the real-time quick test, making the diagnosis of CJD highly probable. This case illustrates the complexities that may arise in diagnosing CJD when pre-existing multimorbidity may cloud the clinical presentation. We also discuss the potential mechanisms underlying the co-occurrence of three rare conditions (situs inversus totalis, Churg Strauss syndrome, CJD) in one patient, taking into consideration the possibility of coincidence as well as common underlying factors. Conclusions The diagnosis of CJD may be easily missed when its clinical symptoms are obscured by those of pre-existing (rare) multimorbidity. This case highlights that when the multimorbidity has neurological manifestations, an extensive evaluation remains crucial to establish the diagnosis, minimize the risk of prion-transmission and provide appropriate guidance to patients and their caregivers.